Prototipo de un sistema de control y monitoreo para la dosificación de químicos en una planta de tratamiento de aguas lluvias (2020)
In this project we present how to do a prototype to control and monitor the system for the dosage of chemicals presenting the problem, the solution, design and manuals for the company Asercampo LTDA. This company works with wastewater and rain treatment to convert it in drinking water. Asercampo LTDA expresses a problem regarding the dosage of the chemicals needed for the rainwater treatment plant located at Alkosto 170 in Bogotá D.C. for this reason, it is necessary a daily control and monitoring system of the dosage of the chemicals. This would us to obtain the quality of water suitable for human consumption and expected by the company Asercampo LTDA and Alkosto 170. Due to internal problems, Alkosto ended the contract with Asercampo, which restricts the implementation at the site, so a detailed design of the project was carried out.